Personalising hand gesture computing - Dilworth, Marie (2017)
Hand gesture recognition has long held a place in science fiction writing and film, and for many years work has continued to develop and improve hand and body gesture recognition for computing, and in particular for computer games. Despite the efforts going into this field, the ability to effectively communicate with computer systems using hand gestures remains elusive. This study seeks to investigate the opportunities and challenges present in the field of hand gesture computing by conducting an experiment in user driven gesture creation, recording and recognition. This study introduces a simple algorithm for the real-time recording and recognition of dynamic hand gestures using the Leap Motion infrared sensor and Unity games development environment.